2002
DOI: 10.1023/a:1020641400589
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We performed a series of meta-analyses examining the associations between coping and health-related outcomes in nonclinical adult samples. Results revealed that problem-focused coping was positively correlated with overall health outcomes, whereas confrontive coping, distancing, self-control, seeking social support, accepting responsibility, avoidance, and wishful thinking were each negatively correlated with overall health outcomes. Neither planful problem solving nor positive reappraisal was significantly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
297
5
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 767 publications
(340 citation statements)
references
References 51 publications
25
297
5
13
Order By: Relevance
“…These findings partially agreed with those reported by Lo [26] , where students used both PFC and EFC in three training courses without any significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings partially agreed with those reported by Lo [26] , where students used both PFC and EFC in three training courses without any significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…The results also indicated that problem-focused coping was used significantly more by students than emotion focused coping, which coincided with the results reported in most of the reviewed studies [17][18][19][20] but differed from studies in which the most commonly-used strategies were emotion focused coping strategies [24,25] or those that reported not differences [26] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Research suggests that, compared to emotion-focused strategies, problem-focused coping tends to assist people in dealing with stressors in more constructive ways (Penley, Tomaka & Wiebe, 2002). However, in real-life circumstances, people are inclined to use a combination of problem-focused and emotion-focused coping strategies (Govender et al, 2015;Ramesar et al, 2009 There is literature to suggest that maladaptive coping, such as using non-prescribed medication and alcohol, and avoidance could negatively impinge on academic performance, self-esteem and well-being (Govender et al, 2015;Penley et al, 2002).…”
Section: "I Will Do Things That I Enjoy Like Going To a Movie Or Danmentioning
confidence: 99%
“…However, in real-life circumstances, people are inclined to use a combination of problem-focused and emotion-focused coping strategies (Govender et al, 2015;Ramesar et al, 2009 There is literature to suggest that maladaptive coping, such as using non-prescribed medication and alcohol, and avoidance could negatively impinge on academic performance, self-esteem and well-being (Govender et al, 2015;Penley et al, 2002). A significant proportion of participants (173/225) pointed to meaning-making as a coping strategy.…”
Section: "I Will Do Things That I Enjoy Like Going To a Movie Or Danmentioning
confidence: 99%